Association between higher mortgage payment-to-income ratio and greater psychological distress among high-income homeowners in Japan: A cross-sectional study - Kazuya Ogawa; Keiichi Shimatani; Ryotaro Iwayama; Norimichi Suzuki (Preventive Medicine Reports)
Objective: While the relationship between higher housing cost burden and poorer mental health has been established in lower-income groups, research examining high-income populations is scarce. We aimed to examine this relationship among high-income homeowners in Japan. Methods: We conducted a cross-sectional study on 6753 Japanese homeowners in detached houses. Data were collected as part of an ongoing panel survey, from new survey respondents during Wave 2 (Jul-Sept 2023) and Wave 3 (Jan-Mar 2024). Psychological distress, measured using the Kessler 6 scale, was the dependent variable. The explanatory variable was the mortgage-to-income ratio, categorized into two and six levels. We performed modified log Poisson regression analyses, incorporating income stratification, with missing data handled by multiple imputation. Results: For both overall respondents (PR = 1.22, 95 % CI 1.11–1.35) and the high-income group (PR = 1.23, 95 % CI 1.09–1.39), individuals with mortgage payment ratios ≥30 % were more likely to report psychological distress compared with those <30 %. While the low-income group showed a marginally similar tendency (PR = 1.21, 95 % CI 1.00–1.46), this association was not robust in the sensitivity analysis. Conclusion: Higher mortgage payment ratios were associated with greater psychological distress even among high-income homeowners. The impact of housing cost stress on psychological distress may be more extensive than previously recognized.